2016
DOI: 10.1161/jaha.115.002330
|View full text |Cite
|
Sign up to set email alerts
|

Nationwide Hospitalization Trends in Adult Congenital Heart Disease Across 2003–2012

Abstract: BackgroundWe aimed to assess trends in hospitalization, outcomes, and resource utilization among patients admitted with adult congenital heart disease (ACHD).Methods and ResultsWe used the 2003–2012 US Nationwide Inpatient Sample for this study. All admissions with an ACHD were identified using standard ICD codes. Resource utilization was assessed using length of stay, invasive procedure utilization, and cost of hospitalization. There was a significant increase in the number of both simple (101%) as well as co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

7
70
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 99 publications
(78 citation statements)
references
References 15 publications
7
70
0
1
Order By: Relevance
“…HF is now a major focus in ACHD specialist care worldwide, accounting for up to one third of all ACHD hospitalizations 6, 16. The 91% increase in ACHD HF hospitalizations observed in this study reflects not only an expansion of the overall population with ACHD but an increasing burden of late‐onset HF often occurring years after surgical repair.…”
Section: Discussionmentioning
confidence: 65%
See 2 more Smart Citations
“…HF is now a major focus in ACHD specialist care worldwide, accounting for up to one third of all ACHD hospitalizations 6, 16. The 91% increase in ACHD HF hospitalizations observed in this study reflects not only an expansion of the overall population with ACHD but an increasing burden of late‐onset HF often occurring years after surgical repair.…”
Section: Discussionmentioning
confidence: 65%
“…For the population with adult CHD (ACHD), heart failure (HF) is now the leading cause of mortality2, 3 and accounts for almost one third of deaths 4. Our nascent understanding of ACHD‐related HF is largely restricted to observational studies and outcomes reported by tertiary ACHD centers,3, 5 an important limitation because many ACHD hospitalizations occur in smaller hospitals with less exposure to ACHD 6. Studies of nationwide ACHD hospital admissions have provided preliminary insights into ACHD HF hospitalization trends,6, 7 but without sufficient detail to inform existing HF services or to anticipate future health resource needs.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…9,10 However, information is limited regarding resource utilization patterns for patients with ACHD specifically at the end of life. The time period near the end of life is associated with costs well beyond the day-to-day cost of care for patients with chronic illness and can be associated with unwanted or burdensome intensity of care.…”
Section: Introductionmentioning
confidence: 99%
“…As compared to GUCH subjects aged between 20 and 60 years, those over 60 years of age need greater healthcare resources as outlined by considering the number of outpatient clinic visits and number and length of hospitalization of these patients [2]. The cardiovascular causes of admission to the hospital depend on complexity of CHD: congestive heart failure is the most frequent condition induced hospital admission and it is more frequent in patients suffering from complex disorders, including tetralogy of Fallot, truncus arteriosus and transposition of great arteries; valvular disease related cardiac decompensation is found in patients with simple disorder without atrial septal defect (ASD) or patent foramen ovale; finally, cerebrovascular event are the main cause of admission in case of patients suffering from simple atrial septal defect or patent foramen ovale [3]. Pulmonary arterial hypertension (PAH) represents an important complication of CHD, affecting about 10% of GUCH patients [4].…”
mentioning
confidence: 99%